Effectiveness of Gargle with Turmeric (Curcuma longa) to Relieve Pain From Caries in Children - Mutmainnah, Baiq; Herdiansyah, Diky (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Turmeric (Curcuma longa) as a remedy for tooth decay pain contains curcumin which has anti-inflammatory and analgesic properties. The purpose of this study was to determine the effectiveness of turmeric concoctions to relieve tooth decay pain in children. This study used a quasi-experimental method with a pretest-posttest design to determine the effectiveness of turmeric concoctions to relieve tooth decay pain in children aged 10-12 years in Aiq Are hamlet. The sampling technique used purposive sampling with a sample size of 30 children. Data collection in this study used an examination sheet by directly examining the children. Data analysis used statistical tests using paired sample t-tests. The results of this study obtained changes in children who consumed turmeric concoctions to relieve tooth decay pain. Changes from 30 children with toothaches were 18 children (60%) no longer had toothaches and 12 children (40%) felt toothache after gargling with turmeric concoctions twice a day, namely in the morning and evening. Statistical tests showed that there was a significant effectiveness of gargling with turmeric concoctions twice a day in relieving tooth decay pain in children with a significance value of 0.000. Gargling with a turmeric concoction can be an alternative to relieve toothache pain in children. Research has shown that turmeric concoctions significantly contribute to toothache pain relief and oral health.